2007
DOI: 10.1002/gcc.20487
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profile of chronic myelogenous leukemia: Imbalances associated with disease progression

Abstract: The expression of the chimeric BCR/ABL1 fusion gene resulting from t(9;22)(q34;q11) in chronic myelogenous leukemia (CML) is necessary for malignant transformation, but not sufficient to maintain disease progression. The appearance of various chromosomal and molecular alterations in the accelerated and terminal phase of CML is well documented, but evidence for causal relationship is largely lacking. We carried out a genome wide screening at a resolution of 1 Mb of 54 samples at different stages of CML together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…In chronic myeloid leukemia patients, specific chromosomal alterations, losses and gains were unique to cases with clinically manifested or suspected accelerated/blast stage. 18 To our knowledge, this is the first study showing an aCGH pattern for patients with aUPD involving part of or the entire HLA region. The technique also revealed constitutive or de-novo microdeletions or gains at 6p21 in four of the six patients.…”
Section: Discussionmentioning
confidence: 78%
“…In chronic myeloid leukemia patients, specific chromosomal alterations, losses and gains were unique to cases with clinically manifested or suspected accelerated/blast stage. 18 To our knowledge, this is the first study showing an aCGH pattern for patients with aUPD involving part of or the entire HLA region. The technique also revealed constitutive or de-novo microdeletions or gains at 6p21 in four of the six patients.…”
Section: Discussionmentioning
confidence: 78%
“…Sex mis-matched reference DNA Both male and female DnA was purchased from Promega UK (Promega, Southampton, UK). the DnA represented a mixture derived from six unrelated disease-free individuals of the same sex, but of unknown ethnic origin, medical history and age (2).…”
Section: Dna Preparationsmentioning
confidence: 99%
“…All procedures were performed as described previously by Brazma et al, (2007) (2). in brief, following hybridization slides were scanned at 10 ”m resolution in a two-channel laser scanner -GenePix 4100B (MDS Analytical Technologies, USA), using GenePix v.6 software generating image (.tiff) and spot analysis (.gpr) files.…”
Section: Imaging Data Analysis and Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazma et al 4 used a bacterial artificial chromosome array with a much lower resolution (1 Mb) and discovered 14 common cryptic abnormalities in CML blast crisis samples that were rare in chronic phase. In a comparison between Ph-positive acute lymphoblastic leukaemia and CML, Mullighan et al 5 used a higher-resolution 250 k SNP array and observed up to 8 CNAs per patient (range 0-8) in a cohort of 23 chronic phase CML samples, but no recurrent aberrations were detected and the authors did not specify whether samples had been taken at diagnosis or later in chronic phase.…”
mentioning
confidence: 99%